A cyclometallated iridium(iii) complex with multi-photon absorption properties as an imaging-guided photosensitizer. Issue 30 (20th July 2022) - Chen, Dandan; Zhao, Hongqing; Shao, Tao; Lu, Xin; Fang, Zhiyun; Cao, Hongzhi; Tian, Yupeng; Tian, Xiaohe
Abstract : The cyclometallated iridium(iii ) complex (Ir-Biotin) with multi-photon absorption and cancer-cell-specific targeting properties exhibits good photodynamic effects as a photosensitizer. Abstract : Conventional photosensitizers (PSs) often have shorter excitation wavelengths and poor cancer cell targeting, resulting in a limited tissue penetration depth and increased biotoxicity, which are significant barriers to ensuring effective photodynamic therapy (PDT) in vivo. In this work, a cyclometallated iridium(iii ) complex (Ir-Biotin) with a long excitation wavelength and effective cancer cell targeting was designed and synthesized. The initial in vitro assessment indicated that Ir-Biotin shows excellent PDT activity with a high singlet-oxygen ( 1 O2 ) generation yield (0.19) due to the facilitated intersystem crossing process. Further study shows that Ir-Biotin shows good biocompatibility, has specific selectivity for cancer cells, and can induce apoptosis under laser irradiation. Furthermore, Ir-Biotin can be applied for imaging-guided PDT using an in vivo imaging system, and showed significant anti-tumour effects (tumour growth inhibition value: 87.66%). These results reveal the importance of long excitation wavelengths of photosensitizers for efficient PDT and suggest a promising strategy for developing effective photosensitizers.